Pengembangan Media Pembelajaran Pop-Up Book Muatan IPA Pada Materi Sistem Tata Surya - Anwar, Anwar; Dewi, Nurul Kemala; Rahmatih, Aisa Nikmah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The learning process carried out by students in grade VI of SDN 2 Kekeri shows challenges in understanding the material. This is due to the lack of use of innovative learning media, so that the learning process tends to be monotonous and students have difficulty understanding abstract concepts. This study aims to develop and describe the validity and practicality of Pop-Up Book learning media in the science content of the Solar System material. This media focuses on the solar system material, designed with three-dimensional and interactive elements such as QR Codes connected to learning videos, 3D animations, and game applications. This type of research is Research and Development (R&D) using the Hannafin & Peck development model which consists of three stages: needs analysis (needs assessment), design (design), and development and implementation (development and implementation). The results of research and development of Pop-Up Book media on solar system material from media experts were 91.25% (Very Appropriate), the results from material experts were 98.75% (Very Appropriate), the results from teacher responses were 95% (Very Practical), the results of student responses in small group tests were 96.25% (Very Practical) and large groups were 95% (Very Practical). This shows that the Pop-Up Book learning media is declared valid and practical for use in science learning on Solar System material.